Prioritising customer-focused KPIs for home furniture delivery and assembly service using AHP: A case study of a multinational company in Thailand - Jaisankad, Rattikan; Tunyaplin, Suratin; Supeekit, Tuangyot; Chanpuypetch, Wirachchaya (Engineering and Applied Science Research, 2022)
Nowadays, e-commerce is growing continuously. This has resulted in a significant demand for last-mile delivery services in various business sections to deliver goods to customer homes. For a retail home furnishings business, the last-mile delivery service for this business is specific and different from other parcels. Since furniture can be large, heavy and may require assembly services. Moreover, it is necessary to make an appointment with the customer to determine the exact date and time of service. Front desk staff, drivers, and assembly workers must communicate with customers directly in several stages of the service. Accordingly, customer dissatisfaction can occur with many service activities. This affects the business performance of the last-mile service provider. Thus, the objective of this article is to identify and prioritise customer-focused key performance indicators (KPIs) of last-mile delivery and assembly services for home furniture products. First, customer-focused performance measures were obtained from a literature review and derived from the Supply Chain Operations Reference (SCOR) model regarding reliability (RL) and responsiveness (RS). These measures were then filtered out identify the KPIs through in-depth interviews with experts in the field. Next, the set of customer-focused KPIs was applied to a multinational company (MNC) in Thailand that provides home furniture delivery and an assembly service. The weights were evaluated by their customers and the respondents who have sufficient experience in home furniture delivery and assembly service through the pairwise comparison method with the AHP technique. Finally, the priority-ranking list of KPIs was obtained which can be used as a tool to improve service performance and customer satisfaction and lead to specify a business strategy. Furthermore, the MNC can apply this approach to re-evaluate the priority weight of customer-focused KPIs for other countries where the company operates such service.